Mathematical Modeling of Indications for Reconstructive Surgery of the Hip Joints in Patients with Cerebral Palsy - Yatsuliak, M.B. (TERRA ORTHOPAEDICA, 2022)
Summary. Relevance. Early detection of hip pathology in patients with cerebral palsy is an effective way to prevent spastic hip dislocation. Objective: to improve the diagnosis of diseases of the hip joints in cerebral palsy through the clinical and radiographic screening based on mathematical modeling. Materials and Methods. The total number of patients was 47 (86 joints). We carried out a clinical and radiographometric examination of the hip joints with our own method and using standard anteroposterior radiographs, which were used to determine the parameters of the hip joint. Mathematical modeling of indications for reconstructive surgery using logistic regression was also performed. Results. The mathematical model “probability of indications for surgical interventions” was developed on the basis of the studied indicators and factors of influence. Conclusions. A mathematical model for screening of hip joints based on the acetabular angle (AA), neck-shaft angle (NSA), femoral torsion (FT), migration percentage (MP), gross motor function classification system (GMFCS) level, gait, and age is proposed; the accuracy of 90.6% is valid for establishing correct indications for surgery (the critical level of indicators is >16.95 ̊ for AA, >45 ̊ for FT, > 141.63 ̊ for NSA, >30 % for MP, and ≤11 years for age).